Analisis Lingkungan Kerja, Karakteristik Individu dan Motivasi Pengaruhnya Terhadap Kinerja Karyawan (Studi pada PT. Swasta STIE Malangkucecwara Malang) - Astuti, Tita Boedi (Akutansi Bisnis & Manajemen ( ABM ), 2017)
Work environment is where the employees work or perform activities, work environment can bring positive and negative impact for employees in the effort to achieve the results of work, a conducive working environment will bring a good impact for the survival of employees at work, and vice versa Positive impact will can understand individual behaviors such as co-workers, superiors, or subordinates. Individual backgrounds can make individual traits or individual characteristics that bring individuals within an organization's environment, especially the work environment. There is the opinion that motivation is a process that explains the intensity, direction and persistence of an individual to achieve his goals. We know that motivation is the result of interaction between the individual and the situation (in this case the work environment). Good employee performance, reflected in the work environment and motivated good employees too. Performance is the work of quality and quantity achieved by an employee in performing their duties in accordance with the responsibilities given to employees concerned, and performance is the result achieved by employee according to the size applicable to the work in question.